Metal–Phenolic Supramolecular Gelation. (30th September 2016) - Rahim, Md. Arifur; Björnmalm, Mattias; Suma, Tomoya; Faria, Matthew; Ju, Yi; Kempe, Kristian; Müllner, Markus; Ejima, Hirotaka; Stickland, Anthony D.; Caruso, Frank
Abstract: Materials assembled by coordination interactions between naturally abundant polyphenols and metals are of interest for a wide range of applications, including crystallization, catalysis, and drug delivery. Such an interest has led to the development of thin films with tunable, dynamic properties, however, creating bulk materials remains a challenge. Reported here is a class of metallogels formed by direct gelation between inexpensive, naturally abundant tannic acid and group(IV) metal ions. The metallogels exhibit diverse properties, including self‐healing and transparency, and can be doped with various materials by in situ co‐gelation. The robustness and flexibility, combined with the ease, low cost, and scalability of the coordination‐driven assembly process make these metallogels potential candidates for chemical, biomedical, and environmental applications.